Microcirculatory Function during Endotoxemia—A Functional Citrulline-Arginine-NO Pathway and NOS3 Complex Is Essential to Maintain the Microcirculation - Karolina A. P. Wijnands (MDPI AG, 2021)
Competition for the amino acid arginine by endothelial nitric-oxide synthase (NOS3) and (pro-)inflammatory NO-synthase (NOS2) during endotoxemia appears essential in the derangement of the microcirculatory flow. This study investigated the role of NOS2 and NOS3 combined with/without citrulline supplementation on the NO-production and microcirculation during endotoxemia. Wildtype (C57BL6/N background; control; n = 36), Nos2-deficient, (n = 40), Nos3-deficient (n = 39) and Nos2/Nos3-deficient mice (n = 42) received a continuous intravenous LPS infusion alone (200 μg total, 18 h) or combined with L-citrulline (37.5 mg, last 6 h). The intestinal microcirculatory flow was measured by side-stream dark field (SDF)-imaging. The jejunal intracellular NO production was quantified by in vivo NO-spin trapping combined with electron spin-resonance (ESR) spectrometry. Amino-acid concentrations were measured by high-performance liquid chromatography (HPLC). LPS infusion decreased plasma arginine concentration in control and Nos3−/− compared to Nos2−/− mice. Jejunal NO production and the microcirculation were significantly decreased in control and Nos2−/− mice after LPS infusion. No beneficial effects of L-citrulline supplementation on microcirculatory flow were found in Nos3−/− or Nos2−/−/Nos3−/− mice. This study confirms that L-citrulline supplementation enhances de novo arginine synthesis and NO production in mice during endotoxemia with a functional NOS3-enzyme (control and Nos2−/− mice), as this beneficial effect was absent in Nos3−/− or Nos2−/−/Nos3−/− mice.